The Performance of Malaysian Unit Trust Funds that is in compliant with Shari’a Principles and Factors Influencing It / Hasimah Omar and Nur Izati Zainal - Omar, Hasimah; Zainal, Nur Izati (2014)
This project paper has been conducted for the purpose of studying Malaysian Unit Trust Funds that is in Compliant with Shari'a Principles and factors that affect the performance. There are four independent variables in this study which are nature and characteristics, professional management, strategies and benefit and market efficiency. Meanwhile, the dependent variable is performance of Islamic unit trust. A set of questionnaire were distributed to 100 respondents that are publics at Kelana Jaya and Sri Petaling through simple random sampling method. Multiple regression analysis was being used to test the hypothesis. The findings revealed that two independent variables that are nature and characteristics and professional management could be used to reliably predict performance of Islamic unit trust due to the p-value below 0.05 while the other two independent variables; strategies and benefit and market efficiency shows the greater p-value that is above 0.05. As the result, the finding discovered that nature and characteristics and professional management has a positive relationship with performance of Islamic unit trust while strategies and benefit and market efficiency shows no relationship with the performance of Islamic unit trust.